2021
DOI: 10.3389/fmed.2020.599236
|View full text |Cite
|
Sign up to set email alerts
|

Complement, a Therapeutic Target in Diabetic Kidney Disease

Abstract: Currently available treatments of diabetic kidney disease (DKD) remain limited despite improved understanding of DKD pathophysiology. The complement system is a central part of innate immunity, but its dysregulated activation is detrimental and results in systemic diseases with overt inflammation. Growing evidence suggests complement activation in DKD. With existent drugs and clinical success of treating other kidney diseases, complement inhibition has emerged as a potential novel therapy to halt the progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…Therefore, suppression of the complement system might be a novel therapy for DN 36 . Further study of the role of the complement system in DN might help to initiate new therapeutic approaches 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suppression of the complement system might be a novel therapy for DN 36 . Further study of the role of the complement system in DN might help to initiate new therapeutic approaches 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed previous research has shown that the activation of the alternative and lectin pathways may also be involved in the pathogenesis of DN ( 25 27 ). Given the role of the complement system in the pathogenesis of DN, inhibition of the specific components of the complement system may be an effective therapeutic strategy for DN ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poor metabolic control in hyperglycemia and DKD activates complement mediated by lectin, by the glycation of pattern recognition molecules [ 57 ]. These changes lead to the dysregulated activation of the complement system.…”
Section: Complement Systemmentioning
confidence: 99%